Transcatheter aortic valve implantation in a patient with type 0 bicuspid aortic valve with severe stenosis and calcium extending in to LVOT - Adhikari, Chandra Mani; Bogati, Amrit; Timalsena, Birat Krishna; Safi, Md. Sajjad; Thapa, Pratik; Ghimire, Vijay; Yadav, Rahul; Prajapati, Dipanker (Journal of Advances in Internal Medicine, 2025)
Transcatheter aortic valve implantation is the most preferred treatment for aortic stenosis in elderly patients at high surgical risk. We present a case experience of Transcatheter aortic valve implantation using a balloon-expandable Myval transcatheter heart valve in a Type 0 bicuspid aortic stenosis.